Premature mortality attributable to COVID-19: potential years of life lost in 17 countries around the world, January-August 2020 - Pagola Ugarte, Maider; Achilleos, Souzana; Quattrocchi, Annalisa; Gabel, John; Kolokotroni, Ourania; Constantinou, Constantina; Nicolaou, Nicoletta; Rodriguez-Llanes, Jose Manuel; Huang, Qianqian; Verstiuk, Olesia; Pidmurniak, Nataliia; Tao, Jennifer Wenjing; et al. (My University, 2022)
Understanding the impact of the burden of COVID-19 is key to successfully navigating the COVID-19 pandemic. As part of a larger investigation on COVID-19 mortality impact, this study aims to estimate the Potential Years of Life Lost (PYLL) in 17 countries and territories across the world (Australia, Brazil, Cape Verde, Colombia, Cyprus, France, Georgia, Israel, Kazakhstan, Peru, Norway, England & Wales, Scotland, Slovenia, Sweden, Ukraine, and the United States [USA]).
Keywords: COVID-19; Disease burden; Pandemic; Potential years of life lost; PYLL; SARS-CoV-2